Levofloxacin Versus Ciprofloxacin in the Treatment of Urinary Tract Infections: Evidence-Based Analysis - Cao, Dehong; Shen, Yinzhi; Huang, Yin; Chen, Bo; Chen, Zeyu; Ai, Jianzhong; Liu, Liangren; Yang, Lu; Wei, Qiang (Frontiers in Pharmacology, 2021)
Urinary tract infections (UTIs) are one of the most common bacterial infections acquired both in community and hospital. Fluoroquinolones, represented by levofloxacin and ciprofloxacin, are widely used for treatment of UTIs. However, it remains controversial for the comparison between the 2 drugs, which propelled us to conduct the first evidence-based research on this topic. To establish their relative efficacy and safety, we searched Pubmed, embase, and Web of Science for randomized controlled trials (RCTs) for UTIs. A total of 5 RCTs were finally included, involving 2,352 patients and a systematic review and meta-analysis were performed to compare the end-of-therapy and posttherapy clinical success rate, microbial eradication rate and adverse event rate. Jadad score and Review Manager 5.3.0 version were applied respectively to evaluate the study quality and heterogeneity. There was no significant difference between levofloxacin and ciprofloxacin group in end-of-therapy or posttherapy clinical success rate and microbial eradication rate (p > 0.05). As for adverse event rate, the 2 drugs were comparable and both safe for clinical use. Based on one included trial and pharmacological research, we raised hypothesis that levofloxacin was superior to ciprofloxacin for treatment of E. coli-induced chronic bacterial prostatitis (CBP) and it required a further study to prove it.